(untitled) (BIRDEM Medical Journal, 2017)
Background: Intraventricular hemorrhage (IVH) is common among preterm infants as many of them survive with the advancements in neonatal care. Severe IVH may lead to significant morbidity and mortality. The objective of our study is to find out the significant clinical signs of IVH in preterm neonate for early detection by ultrasonography. Methods: This prospective observational study was done in special care baby unit (SCABU), Bangladesh Institute of Research & rehabilitation of Diabetic, Endocrine & metabolic Disorder (BIRDEM) for a period of one year. Eighty five preterm neonates were included in this study. Clinical features of IVH like- convulsion, lethargy, irritability, bulged fontanelle, recurrent apnea, sudden onset of respiratory distress, sudden pallor and bradycardia were observed. Cranial ultrasound studies were done within 7 days of life in all cases to identify IVH. Result: Mean gestational age of these neonates was 31.31(±2.2) weeks & mean birth weight was 1413.42 (±330.55) gm. Among 85 preterm neonates 21(24.7%) developed IVH, confirmed by ultrasonography of brain. Clinical features like convulsion, bulged fontanel, repeated apnea & sudden pallor were significantly present in IVH group. Conclusion: Intraventricular Hemorrhage constitutes an important cause of morbidity and mortality in neonate. This study showed that clinical features like convulsion, bulged fontanel and sudden pallor had a significant relationship with intraventricular hemorrhage which will help for its early detection. Birdem Med J 2017; 7(3): 194-197